The Effect of Public Health Spending on Health Outcomes: Evidence from Spain Based on Self-Reported Health Status - Navarro-García, Carlos; Sarria-Santamera, Antonio (British Journal of Healthcare and Medical Research, 2023)
In this paper, we analyse the relationship between public health spending and other biological, sociodemographic, lifestyle and health service use determinants on self-reported health status (SRHS). The study is based on individual SRHS data from the 2017 Spanish National Health Survey and public health expenditure in each of the Autonomous Communities in Spain, and is controlled through a series of separate determinants known to affect the health of individuals. The findings indicate that, increased public health expenditure results in a limited but statistically significant reduction in the possibility of reporting good health statuses. But when we consider the Moulton problem, this relationship is not statistically significant. All other individual health determinants are statistically significant.